Association between WOMAC score and 2D:4D ration in women with knee osteoarthritis - Amir, Nurul Fakhri (2016)
Introduction: The main issue in osteoarthritis is the risk of pain and physical disability. Knee osteoarthritis is one of the commonest joint disorders that lead to physical disability. Elderly women experience lower quality of life due to functional limitation and physical disability than male. Main factor that cause physical disability are increasing age, obesity, lack of exercise, previous knee injury and medical comorbidity. In human, finger length ratio (2D:4D) is a sexually dimorphic trait. Generally, males have low 2D:4D ratio; a ring finger that is longer than their index finger. While female typically have high or equal 2D: 4D ratio, index finger longer than ring fingers or the same length. Different digit ratio associated with human physical capability, attitude and characteristic. Previous study suggested that low 2D:4D ratio associated with higher risk to developed knee osteoarthritis in women. Objectives: To determine association between WOMAC score, Body Mass Index (BMI) with 2D:4D ratio in women with grade 2 and 3 of knee osteoarthritis. Patients and Methods: We conducted cross sectional study in 118 women with knee osteoarthritis (Kellgren Lawrence grade 2 -3), who completed the Western Ontario and McMaster Osteoarthritis Index (WOMAC) questionnaire. Length of index finger and ring finger were measured from right hand radiographs. Subjects were classified into three groups: type I (index finger longer than ring finger), type II (equal length) and type III (index finger shorter than ring finger). Body Mass Index (BMI) was measured and recorded by standard procedure.Result: The majority of the participants were classified under type III finger pattern n=56 (47%). However, this study showed there was no significant mean difference between mean total WOMAC score and each component with 2D:4D ratio. BMI correlated significantly with worse knee OA symptoms for total WOMAC score (pvalue< 0.001, r = 0.643). There was a significant association between 2D:4D ratio and Body Mass Index (BMI) (F-stat (df) 4.38 (2), P-value 0.015) and higher BMI majority in type II (mean (SD) 30.2 (4.31)). Conclusion: There is no association between WOMAC score and 2D:4D ratio in women with grade 2 and 3 of knee osteoarthritis. It means that different type of finger pattern does not affect the severity of physical disability. However, the study showed positive correlation between total WOMAC score and higher Body Mass Index (BMI) and significant association between 2D:4D ratio and higher Body Mass Index (BMI). Those with higher Body Mass Index (BMI) majority in type II